Control químico de enfermedades en el cultivo de maíz (Zea Mays) hibrido emblema, con diferentes combinaciones de fungicidas y estados fenológicos de la planta - Palomino Sánchez, Andrés Francisco (2022)
Ecuador sows large extensions of corn, this crop like others is affected by different diseases that can damage the plantation lowering yields, this research aimed to study the chemical control of diseases in the corn crop (Zea mays) hybrid Emblema, with different combinations of fungicides and phenological stages of the plant